Informed consent and participant perceptions of influenza vaccine trials in South Africa. Issue 12 (30th November 2005) - Moodley, K; Pather, M; Myer, L
Abstract : Background and objectives: There are few insights from sub-Saharan Africa on research participants' experiences of the informed consent process, particularly in the context of randomised controlled trials, where issues of randomisation and the use of placebos may be confusing concepts for participants. This study investigated the knowledge and perceptions of the informed consent process among individuals participating in influenza vaccine trials in two disadvantaged communities in South Africa. Method: Four to 12 months after completion of the trials, participants were contacted to return to participate in the informed consent study. The semistructured questionnaire administered to assess recall of trial procedures and the informed consent process covered key issues including: purpose of the study; awareness that the study was not part of routine treatment; voluntary nature of participation and freedom to withdraw; randomisation; placebos; and remuneration. Results: A total of 334 participants (93% of the original vaccine trial sample; mean age 68 years, median level of education grade 8, 69% women) completed the questionnaire. Only 21% were able to recall that they were allocated randomly to the different treatment arms. Only 19% of those involved in the placebo controlled study had interpreted the concept of placebo as an inactive medication. Conclusion: Although a good general recall of trial concepts was demonstrated, only a small proportion of the participants correctly interpreted and recalled the concepts of randomisation and placebos. Informed consent in this and similarly disadvantaged communities may often be inadequate and new ways to improve understanding of the research process should be explored.